FROM CONTEXTUAL NEED TO DESIGN SOLUTION: A NOVEL CHAIR DESIGN FOR INDIAN DESIGN STUDENTS - Srivastava, Abhishek; Paul, Nandadeep; Atreya, Sonal (ShodhKosh: Journal of Visual and Performing Arts, 2026)
In many Eastern cultures (like India), floor sitting, particularly in postural instances like Indian cross-legged position (locally known as pālathī), has been deeply rooted in daily life. However, as global lifestyles evolve and the influence of Western furniture design spreads, there has been an increasing shift towards the use of chairs. This transition has created a unique challenge in designing seating that accommodates both traditional floor-based postures and modern chair-based postures. However, current seating options generally cater to either elevated sitting or ground-based activities but rarely offer a solution that seamlessly integrates both. This gap is particularly evident in environments such as design classrooms, where versatile seating is crucial. This study reinforces the discussed gap by investigating the literature, market, patents, and through an observational study among design classrooms. Further, A novel chair design is conceptualized for the design students in the Indian context which facilitates conventional sitting as well as Indian cross-legged sitting postures, while allowing multiple seating options like- stool, floor seating, elevated seating along with features like- storage and carry on. The proposed chair is also analyzed using Ansys software for structural robustness under various load tests. Thus, the new design with several benefits and advantages, holds immense potential for introduction in the design classrooms and studios. The solution is also scalable to offices which are now encouraging employee-centric seating preferences; and within household contexts with remote work culture on the rise.